An Introduction to Plum Blossom Boxing: History, Culture and Practice - Zhang, Guodong; Green, Thomas A. (Revista de Artes Marciales Asiáticas, 2012)
Meihuaquan (“Plum Blossom Fist [Boxing]”) has traditionally been practiced as vernacular (folk) art practiced among the Han ethnic group residing in the Shandong, Henan and Hebei Provinces of China. Historical documentation dates Plum Blossom Boxing to the seventeenth century. The classic Chinese novel, Shuihu Zhuan (Marsh Chronicles) recounts the martial exploits of Shandong’s twelfth century outlaw heroes who may have been Mei Boxers, also. Thus, for perhaps a millennium, the region has been noted for vernacular martial arts and social banditry. The region’s rampant lawlessness promoted highly-developed martial prowess among both lawbreakers and those who were required to protect themselves against the brigands. Cultural, economic, and environmental factors in the region gave rise to heterodox political and religious beliefs that frequently served as a catalyst for martial sects, most notably the “Boxers” who at the turn of the twentieth century, came into conflict with the imperial government. These factors laid the groundwork for the “character traits” of the art while Taoism, the Five Elements theory, and a concept of predictable change shaped Plum Boxing’s strategic and mechanical principles. In the past decade, there have been efforts to globalize this vernacular martial art. Rather than driving Plum Boxing to extinction it is likely that the folk and the “larger than local” will co-exist.